Eliciting Antigen-Specific Egg-Yolk IgY with Naked DNA - Marco Romito; Gerrit J. Viljoen; Dion H. Du Plessis (BioTechniques)
Immunization with naked DNA was used to elicit chicken egg yolk antibodies (IgY). Layer hens were inoculated with plasmid DNA encoding the enhanced green fluorescent protein, the fusion protein of Newcastle disease virus, and VP2 of African horse sickness virus. IgY was extracted from egg yolks by polyethylene glycol precipitation. Specific antibodies were present in the yolks of eggs from hens immunized with each of the three different plasmids. This approach to raising polyclonal antibodies obviates the need to produce and purify large quantities of proteins for immunization and can potentially yield large amounts of diagnostically or therapeutically useful reagents.